Electronic Media as a Tool for Government Transparency and Accountability - Abdulhadi, Alaa Makki; AlAli, Fawzia Abdulla (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aimed to explore the impact of digital media usage on daily government activities in the United Arab Emirates. It also examined its role in enhancing government transparency and accountability, as well as its contribution to achieving government accountability. Methodology: A questionnaire was distributed to 254 officials and managers across various government institutions. A stratified random sampling method was applied to ensure a comprehensive and accurate representation of all government sectors. Data collected from the questionnaires was analyzed to evaluate the effectiveness of digital media and identify obstacles hindering its optimal use. Results: The results revealed that digital media significantly improved government efficiency and enhanced transparency. It demonstrated considerable potential to increase productivity, improve communication among government institutions, and enhance the efficiency of government procedures. However, the study identified challenges, such as the need for technological infrastructure improvements and continuous training for government employees. Conclusion: The study concluded that digital media is an effective tool for improving government performance and enhancing transparency and accountability. Addressing the identified challenges is essential for maximizing its benefits.